2016
DOI: 10.9778/cmajo.20150055
|View full text |Cite
|
Sign up to set email alerts
|

Profile of tobacco users identified in primary care practice and predictors of readiness to quit: a cross-sectional survey

Abstract: Background:The aim of this study was to document the prevalence of tobacco use and describe the characteristics of tobacco users identified in primary care practices. Methods:We conducted a cross-sectional survey in 49 primary care practices in the province of Ontario. Consecutive patients were screened for smoking status at the time of their clinic appointment. Patients reporting current tobacco use completed a survey, which documented sociodemographic and smoking-related characteristics. Multilevel modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Second, it is important to promote the use of evidence-based cessation support among smokers, in particular those motivated to make a quit attempt. Previous research has shown that smokers may be unaware of the effectiveness of cessation methods or underestimate their benefits 40-42 , which might be reflected in the high prevalence of unassisted quitting 16,43 . It is notable that the most popular cessation aids in our study were e-cigarettes, although the evidence for their effectiveness is modest.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is important to promote the use of evidence-based cessation support among smokers, in particular those motivated to make a quit attempt. Previous research has shown that smokers may be unaware of the effectiveness of cessation methods or underestimate their benefits 40-42 , which might be reflected in the high prevalence of unassisted quitting 16,43 . It is notable that the most popular cessation aids in our study were e-cigarettes, although the evidence for their effectiveness is modest.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Indeed, nicotine dependence measures such as the number of cigarettes smoked per day and smoking the first cigarette of the day within 30 minutes of awakening are strongly correlated with the intention and outcome of quit attempts. [6,7] The relationship between nicotine dependence and smoking (or smoking cessation) is not simply linear but modulated by other influences such as socioeconomic status (SES) and other lifestyle behaviours that pose a risk to health. [8] In developed countries, not only do people of lower SES smoke more and have a higher level of nicotine dependence, [9] they are also less likely to quit than people of higher SES.…”
Section: Researchmentioning
confidence: 99%
“…To our knowledge, no study has compared, in any population, the efficacy of a smoking cessation program that tailors the intervention goals to the readiness level of participants. While the readiness rate of smoking among cancer survivors is slightly higher (33%) than that of the general smoking population (20%–30%), 25 , 26 the majority of cancer survivors are not ready to make a cessation attempt in the next 30 days. Future research is needed to compare the effectiveness of traditional smoking cessation programs with rate reduction programs among cancer survivors.…”
Section: Discussionmentioning
confidence: 96%